2007
DOI: 10.1134/s1063778807110014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of changes in the rate of beta decay of radioactive elements

Abstract: The experimental data on continuous investigation of changes in β-decay count rate of 137 Cs and 60 Co from 9.12.98 till 30.04.99, are presented. The 27-day and 24-hour periods in these changes, inexplicable by traditional physics, have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 4 publications
3
57
0
Order By: Relevance
“…They concluded that there is serious evidence of solar influence on decay rate [3]. Other experimental results confirming this conclusion have been also presented [4,5]. …”
Section: Motivationsupporting
confidence: 71%
“…They concluded that there is serious evidence of solar influence on decay rate [3]. Other experimental results confirming this conclusion have been also presented [4,5]. …”
Section: Motivationsupporting
confidence: 71%
“…If we find that, for some isotopes, the timing of decays does not conform to the expectations of this model, we must question these assumptions. One would then need to consider the possibilities that decays may be due in part to a cosmological particle or radiation flux, as has been suggested by Baurov et al (2007), or that the axis of rotation of the solar core is not parallel to that of the photosphere.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has uncovered evidence of an unexpected periodicity in several nuclear decays [2,3,4,5,6]. An examination of the periodic behavior exhibited by the data indicated that the primary frequency observed in each data set corresponded to a period of close to one year [7,8].…”
Section: Introductionmentioning
confidence: 99%